Bioenergy Project Activities Through the Structural Funds Programme and the Investment Plans in Finland - Ranta, Tapio; Laihanen, Mika; Karhunen, Antti (European Journal of Applied Sciences, 2025)
The EU’s regional and structural policy has been ongoing in Finland since 1995. The goal of the regional and structural policy is to equalise the developmental and welfare differences between regions and ensure the sustainable growth and competitiveness of the European Union and its member countries. This study is a review of regional and structural policy programme project activities targeting the bioenergy sector during the funding period 2021-2027. A total of 155 bioenergy projects have been launched with a total budget of 64 million euros. The projects focused particularly on biorefining, with biogas and biocoal as end products. The Structural Fund project activities were focused in particular in Eastern and Northern Finland, but more investments were made in Southern and Western Finland. As of 2025, bioenergy investment project proposals worth 10,246 million euros with an employment impact of 6,600 person-years have been submitted, half of which have already received investment or an investment decision has been made. The most significant of these investments are biorefinery and bioproduct factory investments.